2023
DOI: 10.3389/fimmu.2023.1062086
|View full text |Cite
|
Sign up to set email alerts
|

Improved efficacy of mesenchymal stromal cells stably expressing CXCR4 and IL-10 in a xenogeneic graft versus host disease mouse model

Abstract: Previous clinical trials have shown that mesenchymal stromal cells (MSCs) can modulate graft versus host disease (GvHD) after allogeneic hematopoietic transplantation, although with variable efficacy. To improve the anti-GvHD effect of these cells, adipose tissue derived-human MSCs (Ad-MSCs) were transduced with a lentiviral vector conferring stable expression of CXCR4, a molecule involved in cell migration to inflamed sites, and IL-10, a cytokine with potent anti-inflammatory properties. In vitro experiments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Enhancing Sdf1 and Cxcr4 expression has been shown to promote the mobilization and homing of MSCs. While viral transduction, drug pretreatment, and gene editing are important methods to explore in promoting expression of Sdf1 and Cxcr4 , they may not currently be feasible in clinical practice [ 12 , 43 , 44 ]. Moxibustion, an external treatment used in traditional Chinese medicine, is popular in clinical practice and is easy to use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enhancing Sdf1 and Cxcr4 expression has been shown to promote the mobilization and homing of MSCs. While viral transduction, drug pretreatment, and gene editing are important methods to explore in promoting expression of Sdf1 and Cxcr4 , they may not currently be feasible in clinical practice [ 12 , 43 , 44 ]. Moxibustion, an external treatment used in traditional Chinese medicine, is popular in clinical practice and is easy to use.…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) have emerged as potential therapeutic candidates for ovarian aging [ 10 , 11 ]. A recent study provided clinical evidence that substantiated the effects of MSCs in improving ovarian response, pregnancy rate, and live birth rate [ 12 ]. Bone marrow mesenchymal stem cells (BMSCs) are advantageous owing to their easy accessibility and low immunogenicity [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of other chemokine receptors such as CXCR7 or the α4 chain of VLA-4 integrin, has demonstrated an improved MSC homing to inflamed/injured tissues [53,54]. Levy et al aimed to enhance the ability of MSCs to tether and roll over endothelium by transfecting these cells with mRNA for PSGL-1 and sialyl Lewis X (sLeX), which are ligands for P-and E-/L-selectin, respectively [55], while Hervás-Salcedo et al showed that the transient expression of CXCR4 by mRNA transfection improved MSC migration to inflamed tissues [56].…”
Section: Enhancing Msc Homing To Tumour Sitesmentioning
confidence: 99%
“…Interleukin-10 (IL-10), a pleiotropic cell-signaling cytokine, contributes to immune modulation and inflammation [1]. Its production occurs in various lymphocyte subtypes, including macrophages, B cells, granulocytes, dendritic cells, and multiple T cell subsets [2,3].…”
Section: Introductionmentioning
confidence: 99%